Photodynamic therapy: A targeted literature review focussing on outcomes and optimisation in solid organ transplant recipients. (22nd April 2019) - Lim, Chloe M; Gordon, Lynne
Abstract: Squamous cell carcinoma incidence is 65‐ to 250‐fold in solid organ transplant recipients, BCC is 10‐fold and in Australia, rates of skin cancer in solid organ transplant recipients reach 70–82% prevalence within the first 20 years; hence, effective, evidence‐based treatment of early and precancerous lesions is an essential tool in dermatological patient care. Photodynamic therapy is used to treat a range of conditions including actinic keratoses, squamous cell carcinoma in situ, superficial basal cell carcinoma and nodular basal cell carcinoma. A literature review was undertaken to examine the outcomes of photodynamic therapy in solid organ transplant recipients and methods of optimising outcomes in solid organ transplant recipients. Study sizes were small and protocols varied widely, so meta‐analysis was not possible; however, photodynamic therapy appears to be an acceptable treatment for approved indications in solid organ transplant recipients in whom ongoing surveillance is maintained to ensure clearance and detect recurrence. Methods for improving efficacy were also reviewed for this population. Improved outcomes may be achieved by combining photodynamic therapy with other local methods such as 5‐fluorouracil or ablative fractional laser.